THE PRODUCTION CAPACITY OF LEACHATE COLECTED FROM PIATRA NEAMT LANDFILL - MIHAI-COSMIN BELCIU (Alma Mater Publishing House "Vasile Alecsandri" University of Bacau, 2016)
Lately it was seen an growth and range broadening of activities in all sectors of economy and society and therefore, the management of waste is a problem facing the entire planet. This paper purpose an analysis of a Romanian Landfill, concerning leachate production. Mathematical models applied on landfill products create an environmental background in which concerns waste management in Romania.